Pemanfaatan Media Sosial dalam Pembelajaran Agama Islam di Sekolah Menengah: Implikasi dan Strategi Pengembangan Pembelajaran - Syafirna, Farah; Zahrani, Aula Dwi; Ni’am, Muhammad Fathu; Zulika, Nur Rohma; Kunaepi, Aang (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2024)
This study aims to investigate the impact of social media use in the context of Islamic religious learning in secondary schools. By utilizing qualitative research methods, this research explores students' perceptions and experiences as well as teachers' opinions regarding the integration of social media in Islamic religious learning. Findings highlight the positive role of social media in facilitating access to information, expanding the reach of learning, and increasing student engagement. However, research also highlights challenges such as distractions, lack of content control, and the risk of possible negative influences. The implications of these findings provide valuable insights for the development of more effective and sustainable learning strategies in the future. This research explores in depth the impact and implications of using social media in Islamic religious learning in secondary schools. The results show that social media can be an effective tool in facilitating discussions, sharing resources, and enriching learning experiences. However, the findings also illustrate challenges such as distraction, the spread of unverified information, and the risk of misuse of the platform by irresponsible parties. In conclusion, this research highlights the importance of a balanced and thoughtful approach to the use of social media in the context of Islamic religious learning in secondary schools.